Dual analysis of host and pathogen transcriptomes in ostreid herpesvirus 1-positive Crassostrea gigas - Rosani, U; Varotto, L.; Domeneghetti, S.; Arcangeli, G.; Venier, P.; PALLAVICINI, Alberto (Environmental Microbiology, 2015)
Ostreid herpesvirus type 1 (OsHV-1) has become a problematic infective agent for the Pacific oyster Crassostrea gigas. In particular, the OsHV-1 μVar subtype has been associated with severe mortality episodes in oyster spat and juvenile oysters in France and other regions of the world. Factors enhancing the infectivity of the virus and its interactions with susceptible and resistant bivalve hosts are still to be understood, and only few studies have explored the expression of oyster or viral genes during productive infections. In this work, we have performed a dual RNA sequencing analysis on an oyster sample with a high viral load. High sequence coverage allowed us to thoroughly explore the OsHV-1 transcriptome and identify the activated molecular pathways in C.gigas. The identification of several highly induced and defence-related oyster transcripts supports the crucial role played by the innate immune system against the virus and opportunistic microbes possibly contributing to subsequent spat mortality.